Farmers’ Adaptability to Climate Change in Lampung Province - Helvi Yanfika; Indah Nurmayasari; Indah Listiana; R.A. Diana Widyastuti; Maya Riantini; Puspita Yuliandari; Adia Nugraha (Universitas Muhammadiyah Malang, 2022)
This research aims to analyze the impact of climate change on the productivity of rice farming businesses, know the knowledge, attitudes, and adaptability to climate change, and present a review and criticism analysis for product updates related to climate change. The study respondents numbered 100 rice farmers in Lampung Province. The processed data is analyzed by using descriptive statistics, using Crosstabs analysis to calculate the frequency and percentage of two or more variables at once while to see the influence of farmer behavior is using path analysis. The results of this study showed that the impact of climate change greatly affects rice farming businesses which leads to a decrease in the productivity of farmers' rice farming businesses. The lack of knowledge of farmers about climate change and the attitude of farmers in dealing with climate change are great concern, but in the follow-up to curiosity and problem solving tends to be less, this is due to farmers less enthusiastic in determining the attitude of climate change. The level of adaptation of farmers to climate change only occurs when determining planting time, so it needs to increase the power due to climate change. Recommendations from these results, among others, related to regulations that require renewal. This update obtained two perspectives, namely the legal perspective and the perspective of the development of the climate issue itself.